Women and Malaysian Islamic Family Law: exploring the gender sensitive path of jurisprudential reform - Haneef, Sayed Sikandar Shah; Mahmud , Mek Wok (Walter de Gruyter GmbH & Co. KG, 2011)
Modern Islamic family laws in the form of statutory codiﬁed ﬁqh, dated back to Ottoman Law of Family Rights 1917, supposedly was initiated with the prime purpose of overcoming certain juristic doctrines disfavoring women. Nevertheless, from the female perspective, such a statesponsored approach has failed to ameliorate the conditions of women the world over on many aspects including methodological grounds, in spite of some progress towards such an end. The same assertions are made against various state Islamic family law enactments in the Malaysian context. To remedy the situation, given the cultural sensitivity and moorings of different interest groups in the country, the approaches have been diverse. Examining the issue from a purely academic, nonpartisan jurisprudential perspective also points to serious problems of methodology alongside with attitudinal ones. This paper argues that a paradigm shift from the current schoolbound cum eclectic approach to that of gender sensitive jurisprudential choice of the juridical views would be an alternative way to reform the law.